2021
DOI: 10.1111/pce.14055
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular attributes contribute to high night temperature tolerance in cereals

Abstract: Asymmetric warming resulting in a faster increase in night compared to day temperatures affects crop yields negatively. Physiological characterization and agronomic findings have been complemented more recently by molecular biology approaches including transcriptomic, proteomic, metabolomic and lipidomic investigations in crops exposed to high night temperature (HNT) conditions. Nevertheless, the understanding of the underlying mechanisms causing yield decline under HNT is still limited. The discovery of signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 106 publications
(321 reference statements)
2
9
0
Order By: Relevance
“…Our analyses showed that rice phenology responded differently to T min , T max and T mean , and T min affected more significantly the GPs for all the three rice types, which was well supported by chambers and field-based studies in cereals across major cropping regions of the world (Peng et al 2004, Impa et al 2021, Schaarschmidt et al 2021, Sakai et al 2022. The stronger negative effects of T min may mostly result from its greater increasing rate (supplementary figure S3).…”
Section: The Different Effects Of Daily Mean Daytime and Night-time W...supporting
confidence: 77%
“…Our analyses showed that rice phenology responded differently to T min , T max and T mean , and T min affected more significantly the GPs for all the three rice types, which was well supported by chambers and field-based studies in cereals across major cropping regions of the world (Peng et al 2004, Impa et al 2021, Schaarschmidt et al 2021, Sakai et al 2022. The stronger negative effects of T min may mostly result from its greater increasing rate (supplementary figure S3).…”
Section: The Different Effects Of Daily Mean Daytime and Night-time W...supporting
confidence: 77%
“…A new paradigm in the form of metabolomics has emerged as a potential approach to establish signature metabolites as markers associated with agronomically important traits ( Schaarschmidt et al, 2021 ). Metabolite levels are a quantitative trait and hence in QTL mapping and GWAS they are considered as quantitative phenotypic trait.…”
Section: Metabolomics: An Underutilized Technique In Lentil Breedingmentioning
confidence: 99%
“…A large genetic diversity exists in crop plants, with different level of sensitivity observed in response to heat stress, but exploiting higher levels of heat tolerance for crop improvement has been a challenge due to limitations related to phenotyping large populations (Impa et al, 2021). Using metabolomics and transcriptomics approaches, Schaarschmidt, Lawas, Kopka, Jagadish, and Zuther (2021) show the relevance of deriving molecular markers to enhance our ability to capture large genetic diversity for heat stress responses. Schaarschmidt et al (2021) reveal underlying metabolites and transcripts that differentiate heat‐tolerant rice and wheat from susceptible genotypes, indicating the possibility of developing molecular markers to complement ongoing efforts to breed crops with increased heat tolerance.…”
Section: Synthesis Of Plant Responses To Heatmentioning
confidence: 99%
“…Using metabolomics and transcriptomics approaches, Schaarschmidt, Lawas, Kopka, Jagadish, and Zuther (2021) show the relevance of deriving molecular markers to enhance our ability to capture large genetic diversity for heat stress responses. Schaarschmidt et al (2021) reveal underlying metabolites and transcripts that differentiate heat‐tolerant rice and wheat from susceptible genotypes, indicating the possibility of developing molecular markers to complement ongoing efforts to breed crops with increased heat tolerance.…”
Section: Synthesis Of Plant Responses To Heatmentioning
confidence: 99%